You might not be as agile as you think you are - Lindpaintner, Julia; Rivera, Stephanie (2019)
The mandate to be agile is everywhere. But agile isn’t an on-off switc h. It’s a skill and a mindset that is developed over time, through ded icated work, open teams, and lots (and lots) of practice